Association between household solid fuel use and dual sensory impairment in a Chinese population: a retrospective cohort study - Du, Yaolei; Wu, Mengnan; He, Mansha (Frontiers in Public Health, 2025)
AimDual sensory impairment (DSI) is more harmful than a single visual impairment or hearing impairment. We aimed to explore the relationship between household fuel use and the risk of DSI in the middle-aged and older adult Chinese population.MethodsData from the China Health and Retirement Longitudinal Study (CHARLS) 2015 of 8,083 participants aged ≥45 years were used, followed up to 2018. Household fuels include heating fuels and cooking fuels. Participants were divided into four groups based on the type of household fuel use at baseline (2015) and during follow-up (2018) (baseline and follow-up): clean fuels and clean fuels, clean fuels and solid fuels, solid fuels and clean fuels, and solid fuels and solid fuels. Logistic regression models were used to assess the association between household fuel use and the risk of DSI, and odds ratio (OR) with 95% confidence interval (CI) was utilized to evaluate the association.ResultsOf these 8,083 participants, 886 (10.96%) had hearing impairment, 2,361 (29.21%) had visual impairment, and 505 (6.25%) had DSI. The use of solid fuels at baseline (OR = 1.23, 95%CI: 1.02–1.49) was associated with a higher risk of DSI compared to the use of clean fuels. People in the clean fuels and solid fuels group (OR = 1.50, 95%CI: 1.04–2.16) and the solid fuels and solid fuels group (OR = 1.38, 95%CI: 1.10–1.73) were linked to an increased risk of DSI compared to people in the clean fuels and clean fuels group, whereas no significant difference was observed in the effect on DSI between people in the solid fuels and clean fuels group and the clean fuels and clean fuels group (p = 0.99). Subgroup analysis demonstrated that males in the solid fuels and clean fuels group (OR = 0.60, 95%CI: 0.39–0.92) had a lower risk of DSI compared to those in the solid fuels and solid fuels group.ConclusionHousehold solid fuel use is associated with an increased risk of DSI in middle-aged and older Chinese people, and promoting the use of clean fuels is beneficial in reducing the burden of DSI.